Newly designed, simple relief phase contrast for microscopy of microorganisms - Žižka, Zdeněk (Folia microbiologica, 2010)
A new method providing a relief phase contrast for investigation of microorganisms by optical microscopy used a neutral filter Zeiss NG 10/1 that could be controllably slid at a certain azimuthal angle below the aperture condenser diaphragm of the microscope phase contrast. Two ways of application are described depending on the type of the microscope: (1) in a special holder, and (2) fixed on a rubber ring. The device enabled us to obtain excellent results in the area of both optical microscopy and microphotography. With the microorganisms visualized, a better resolution, higher contrast and a significant 3D effect were obtained; outer morphology and organelles (chloroplasts, nuclei, granules, oil reserve vacuoles, etc.) could also be investigated.
Keywords: mikroskopie fázově kontrastní; financování organizované; eukaryotické buňky; organely; Prokaryotic Cells; prokaryotické buňky; Financing, Organized; Eukaryotic Cells; Microbiological Techniques; Organelles; mikrobiologické techniky; Microscopy, Phase-Contrast